2017
DOI: 10.1590/0001-3765201720170068
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic activity of Plectranthus ornatus Codd., a Traditional Medicinal Plant

Abstract: The dichloromethane extract of Plectranthus ornatus Codd., a tradicional medicinal plant, showed antibiotic activity with minimum inhibitory concentration (MIC) values of 0.4 mg.mL -1 and 100 percent of biofilm inhibition against Staphylococcus aureus strains isolated from animals with mastitis infections. Based on these antibacterial activities, in addition to ethnopharmacological reports from healing men and farmers in Brazil, an herbal soap was produced from this active extract and was tested both in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…Silva and collaborators [31], studying the antimicrobial potential of plant extracts, obtained for ethanolic extract of P. ornatus leaves against two strains of S. aureus MIC of 1200 µg/mL. The dichloromethane extract from the leaves of this species, on the other hand, showed good antibacterial potential against S. aureus, with MIC ranging from 500 to 700 µg/mL [32]. These results show low potentials when compared to the results of this study.…”
Section: Antimicrobial Activitycontrasting
confidence: 50%
“…Silva and collaborators [31], studying the antimicrobial potential of plant extracts, obtained for ethanolic extract of P. ornatus leaves against two strains of S. aureus MIC of 1200 µg/mL. The dichloromethane extract from the leaves of this species, on the other hand, showed good antibacterial potential against S. aureus, with MIC ranging from 500 to 700 µg/mL [32]. These results show low potentials when compared to the results of this study.…”
Section: Antimicrobial Activitycontrasting
confidence: 50%
“…The antibacterial use of the traditional medicinal plant Plectranthus ornatus (spur flowers) used in Brazil for treatment of skin infections was investigated for its anti-biofilm properties by using the plant as a herbal soap on gloves contaminated with S. aureus from dairy cows with bovine mastitis. There was no microbial growth after the gloves were submerged in the herbal soap and when the biofilm inhibitory concentration by microtiter plates and crystal violet staining was investigated, the plant was able to inhibit biofilm formation (69). Anti-biofilm agents against S. aureus have also been investigated in vivo.…”
Section: Investigations Of Antimicrobial Compounds Against Biofilm Forming Mastitis Pathogensmentioning
confidence: 99%
“…Most of the so-called in vivo investigations of biofilm in bovine mastitis have used experimental models (mice and sheep), and the majority of these studies focused on anti-biofilm treatment or vaccines against biofilm udder infections (Table 1) (44,69,70,72,(83)(84)(85). Only a few studies investigated and confirmed biofilm in vivo within udder tissue of dairy cows with bovine mastitis.…”
Section: In Vivo Investigations Of Biofilm In Bovine Mastitismentioning
confidence: 99%
“…Gas chromatography/mass spectrometry (GC-MS) analysis was then carried out using a Shimadzu GCMS-QP5050A spectrometer, as suggested by ADAMS (2007). Chromatographic analysis was performed using the parameters described by NASCIMENTO et al (2017). Compounds were…”
Section: Chemical Composition Of Active Essential Oilsmentioning
confidence: 99%